Author Correction: Time-restricted feeding restores muscle function in Drosophila models of obesity and circadian-rhythm disruption - Jesús E. Villanueva; Christopher Livelo; Adriana S. Trujillo; Sahaana Chandran; Brendon Woodworth; Leo Andrade; Hiep D. Le; Uri Manor; Satchidananda Panda; Girish C. Melkani (Nature Communications, 2020)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.